2011
DOI: 10.1007/s11060-011-0711-5
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of real-time in vivo optical detection of blood–brain barrier disruption with indocyanine green

Abstract: Osmotic disruption of the blood-brain barrier (BBB) by intraarterial mannitol injection is sometimes required for the delivery of chemotherapeutic drugs to brain tissue. Osmotic disruption is affected by a number of factors, and there is a significant variability in the degree and distribution of BBB disruption in clinical and experimental settings. Brain tissue concentrations of indocyanine green (ICG) can be measured by optical techniques. The aim of this experiment was to determine whether the disruption of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 35 publications
(54 reference statements)
1
26
0
Order By: Relevance
“…This effect explains delivery in that small molecules may pass through a disrupted tumor blood brain barrier and be retained due a relative lack of drainage (by lymphatics, for example). 14 Prior work has demonstrated that accumulation within may occur due to the relatively hypoxic microenvironment. 15 As a molecule, ICG is amphiphilic; it has 2 ringed groups (1 with positive charge) and 2 negatively charged sulfonate groups.…”
mentioning
confidence: 99%
“…This effect explains delivery in that small molecules may pass through a disrupted tumor blood brain barrier and be retained due a relative lack of drainage (by lymphatics, for example). 14 Prior work has demonstrated that accumulation within may occur due to the relatively hypoxic microenvironment. 15 As a molecule, ICG is amphiphilic; it has 2 ringed groups (1 with positive charge) and 2 negatively charged sulfonate groups.…”
mentioning
confidence: 99%
“…4 Common medical applications include visualization of blood flow in different organs and screening of inflammation in rheumatoid arthritis. [5][6][7][8][9][10][11][12] In ophthalmology, ICG has been used for both diagnostic purposes and surgical interventions. [13][14][15][16] For the former, intravenous injection of ICG into the blood enables retinal and choroidal angiography.…”
mentioning
confidence: 99%
“…Moreover, the NIR fluorescence imaging eliminates autofluorescence from the body, which can increase accuracy of imaging data from animals 11 - 17 . However, the number of approaches demonstrating the feasibility of assessment BBB impairment with NIR fluorescence techniques is limited 1 , 18 , 19 . EBD has the optical property that it becomes a moderate-strength fluorophore emitting at 680 nm when diluted to levels that are almost undetectable to the human eye.…”
Section: Introductionmentioning
confidence: 99%